Psychophysiological training with biofeedback: dynamics of anxiety level of the athletes - Bulynko, Ekaterina S. (Journal of the Belarusian State University. Philosophy and Psychology, 2022)
The article describes the effect of psychophysiological training sessions with biofeedback on the level of situational anxiety in athletes 12–18 years old. High physical activity affects the psychological state, especially on young athletes, since inthis age period they are faced with both age-related normative crises and crises associated with high physical and psychological stress of sports activity. A teenager preparing for a sports competition begins to experience internal stress, which further causes a feeling of anxiety. Situational anxiety in the process of competitive activity is permissible if it does not interfere with the young athlete, but, on the contrary, mobilises him. But everything is different if situational anxiety arises already in the process of training activity. In this case, the athlete spends his mental energy on experiencing this anxiety, and not on physical and technical-tactical training. As a result of psychophysiological training with biofeedback, young athletes are able to regulate anxiety and significantly reduce internal stress.
Keywords: anxiety; youth sports; training activities; psychophysiological training; biofeedback